FORMULASI NUTRASEUTIKAL SEDIAAN GUMMY CANDIES SARI BUAH BELIMBING MANIS (AVERRHOA CARAMBOLA. L) DENGAN VARIASI KADAR MANITOL DAN CORN SYRUP SEBAGAI BASIS - Feris Firdaus; Wina Islamaya; Fajriyanto Fajriyanto (Teknoin, 2014)
Sweet star fruit (Carambola averrhoa L.) is one type of fruit plants that is widespread in Indonesia. Sweet star fruit contained high concentration of vitamin A and vitamin C. Utilization of sweet star fruit as nutraceuticals products that are rich in vitamin A and C are still relatively rare. Demands of people who want to get an interesting kind of preparation and easy to use push of this study which aims to produce gummy candies. Preparations of gummy candies was made in 5 formulations based on a combination of gummy base (mannitol and corn syrup) with a ratio of 50%: 50%, 40%: 60%, 25%: 75%, 60%: 40%, 75%: 25%. Making sweet star fruit juice using freeze drying method then organoleptic test was conducted on the sweet star fruit juice. Testing physical properties of gummy candies include organoleptic test, weight uniformity test, and preference level (hedonict test) by the respondent and then the test results were compared with the requirements in the literature. Formula 3 with gummy base containing ratio of mannitol:corn syrup (25%: 75%) is the best formula that is compared with other formula, with a coefficient of variation for weight uniformity test was 2.09%.